Blood utilization at a national referral hospital in sub‐Saharan Africa. Issue 5 (3rd February 2015) - Butler, Elissa K.; Hume, Heather; Birungi, Isaac; Ainomugisha, Brenda; Namazzi, Ruth; Ddungu, Henry; Kajja, Isaac; Nabadda, Susan; McCullough, Jeffrey
<x xml:space="preserve">Abstract</x> BACKGROUND A safe and adequate supply of blood is critical to improving health care systems in sub‐Saharan Africa, where little is known about the current use of blood. The aim of this study was to comprehensively describe the use of blood at a tertiary care hospital to inform future efforts to strengthen blood programs in resource‐limited settings. STUDY DESIGN AND METHODS Data were collected from blood bank documentation for all units issued at Mulago Hospital Complex in Kampala, Uganda, from mid‐January to mid‐April 2014. RESULTS A total of 6330 units (69% whole blood, 32% red blood cells, 6% platelets, 2% plasma) were issued over the 3‐month study period to 3662 unique patients. Transfusion recipients were 58% female and median age was 27 years (interquartile range [IQR], 14–41). Median pretransfusion hemoglobin was 5.6 g/dL (IQR, 4.0–7.2 g/dL, n = 1090). Strikingly, cancer was the top indication for transfusion (33.5%), followed by pregnancy‐related complications (12.4%) and sickle cell disease (6.9%). CONCLUSION This study provides a comprehensive picture of blood use at a national referral hospital in sub‐Saharan Africa. Noncommunicable diseases, particularly oncologic conditions, represent a large proportion of demand for transfusion services.